2019
DOI: 10.1021/jacs.9b07493
|View full text |Cite
|
Sign up to set email alerts
|

Structural Origin of the Large Redox-Linked Reorganization in the 2-Oxoglutarate Dependent Oxygenase, TauD

Abstract: 2-Oxoglutarate (2OG)-dependent oxygenases catalyze a wide range of chemical transformations via C−H bond activation. Prior studies raised the question of whether substrate hydroxylation by these enzymes occurs via a hydroxyl rebound or alkoxide mechanism and highlighted the need to understand the thermodynamic properties of transient intermediates.A recent spectroelectrochemical investigation of the 2OG-dependent oxygenase, taurine hydroxylase (TauD), revealed a strong link between the redox potential of the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The three reactant complexes Re 1 , Re 2 , and Re 3 have a short Fe–O distance of 1.65 Å, which is expected for the double bond configuration of this complex. These values compare well with the experimental work on analogous nonheme iron enzymes and are similar to related nonheme iron enzyme calculations and biomimetic model complexes calculated previously. Moreover, experimental Mössbauer and resonance Raman spectroscopy on analogous nonheme iron dioxygenases found similar bond lengths and typically a quintet spin ground state for the iron­(IV)-oxo species. In all three reactant structures, the axial histidine ligand was positioned at around 2.06–2.09 Å from the iron (Fe–N ax distance) in the quintet spin state structures.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The three reactant complexes Re 1 , Re 2 , and Re 3 have a short Fe–O distance of 1.65 Å, which is expected for the double bond configuration of this complex. These values compare well with the experimental work on analogous nonheme iron enzymes and are similar to related nonheme iron enzyme calculations and biomimetic model complexes calculated previously. Moreover, experimental Mössbauer and resonance Raman spectroscopy on analogous nonheme iron dioxygenases found similar bond lengths and typically a quintet spin ground state for the iron­(IV)-oxo species. In all three reactant structures, the axial histidine ligand was positioned at around 2.06–2.09 Å from the iron (Fe–N ax distance) in the quintet spin state structures.…”
Section: Resultssupporting
confidence: 88%
“…Because of the difficulties encountered in trapping and characterizing short-lived catalytic cycle intermediates in CsiD and the lack of information on the details of its enzymatic reaction mechanism, we decided to perform a computational study. Previous experimental studies on related enzymes showed that α-ketoglutarate-dependent dioxygenases often operate through the formation of a high-valent iron­(IV)-oxo species as the active oxidant. Indeed, computational studies on nonheme iron/α-KG-dependent dioxygenases the initial reaction of iron­(II) with dioxygen in the presence of a bound α-KG molecule gives an iron­(IV)-oxo species, succinate and releases a CO 2 molecule with large exothermicity. The iron­(IV)-oxo species of several nonheme iron dioxygenases has been characterized by UV–vis absorption, resonance Raman, electron paramagnetic resonance, and Mössbauer spectroscopy methods. , All of these studies identify the iron­(IV)-oxo species as the active oxidant in the substrate activation reaction. Our study therefore starts from the iron­(IV)-oxo species of CsiD, where we took the 6HL9 pdb file and inserted a glutarate ion into the substrate binding pocket with the Autodock Vina program .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the electron-transfer processes in the catalytic reactions, these non-heme iron-containing enzymes can be roughly classified into two main categories, one performs two-electron oxidation of the substrates and the other fully couples the reduction of dioxygen to the four-electron oxidation of the substrates. Fe II /2OG-dependent oxygenases fit into the first category, which carry out a variety of two-electron oxidation processes on the substrates, leading to hydroxylation, halogenation, , dehydrogenation, , and cyclization products. In Fe II /2OG-dependent oxygenases, the substrates do not coordinate to the iron center directly; therefore, the oxidation reaction has to be accomplished through a highly active Fe IV O core. They consequently require cosubstrate 2OG as an exogenous electron resource to provide two extra electrons to reduce dioxygen and to assist to generate the highly active Fe IV O core.…”
Section: Introductionmentioning
confidence: 99%